2023
DOI: 10.1186/s12939-022-01812-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of ethnic differences in the uptake of child healthcare services in New Zealand: a decomposition analysis

Abstract: Background There are persistent ethnic gaps in uptake of child healthcare services in New Zealand (NZ), despite increasing policy to promote equitable access. We examined ethnic differences in the uptake of immunisation and primary healthcare services at different ages and quantified the contribution of relevant explanatory factors, in order to identify potential points of intervention. Methods We used data from the Growing Up in New Zealand birth … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Another significant finding was that when families experienced ethnic discrimination, this was associated with reduced satisfaction levels, and childhood immunisations. 20 , 22 This is consistent with other substantive research that finds that racism and ethnic discrimination are determinants of inequitable immunisation coverage and healthcare access for children and their whānau (family). 23 , 24 , 25 …”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Another significant finding was that when families experienced ethnic discrimination, this was associated with reduced satisfaction levels, and childhood immunisations. 20 , 22 This is consistent with other substantive research that finds that racism and ethnic discrimination are determinants of inequitable immunisation coverage and healthcare access for children and their whānau (family). 23 , 24 , 25 …”
Section: Introductionsupporting
confidence: 85%
“… 16 A quantitative analyses using the GUiNZ study cohort of the uptake of early childhood services showed time-variant differences in the association between ethnicity and child immunisation indicators. 20 , 22 For example, socio-economic deprivation was a significant factor for families not having timely immunisations in the first year of the child's life, but not at the 15-months and 4-year old immunisation events. 20 This suggests that there are socio-economic drivers in the first year of life affect timely access to healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 40 years, a mana-enhancing paradigm has substantially developed with application to various disciplines, including social work, health, and education. 51 Research has noted how HCP recommendations can influence vaccine decisions 15 , 52 and how the COVID-19 pandemic can provide an opportune time for immunization providers to support informed vaccine decision-making among parents. 9 As such, there is the opportunity for HCPs to engage in respectful and mana-enhancing discussions with whānau about vaccines and support intergenerational conversations for collective decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Non-genetic factors however may be more important. Recent research suggests socioeconomic status, mobility and discrimination are strong influences for many health outcomes in Māori 37…”
Section: Discussionmentioning
confidence: 99%